Women in mining worlds : a socio-environmental history of women in artisanal gold mining in Zimbabwe, with specific reference to Mazowe District, c. 1932 to 2021 - Shaba, Jabulani (Stellenbosch : Stellenbosch University, 2024)
Thesis (DPhil)--Stellenbosch University, 2024.